Choroid plexus tumors - Orlov, Yuriy; Shaverskyi, Andrii; Svyst, Аndriy (Ukrainian Neurosurgical Journal, 2012)
Introduction. In the article the data of literature are summarized and age-related features of choroid plexus tumors clinical flow, diagnostics, localization and outcomes in children and adults are considered. Materials and methods. The research is based on retrospective analysis of case reports of patients been treated in Institute for period of 30 years. Results. Choroid plexus tumors — are rare primary neoplasms from neuroepithelial tissue. They make from 0.4 to 1% in structure of all intracranial tumors. Most often they are found in infants. Conclusions. Treatment of these patients is complicated by chorioid plexus tumors’ high vascularity, accompanying hydrocephalus and ineffective adjuvant therapy of choroid plexus carcinomas.